Post-pandemic perspectives in social care. Toward the end of medicine? - Ennio Cocco (Publiediting, 2021)
The debate about residential institutions for the elderly with disabilities (RSA) is back current in the last two years, as a result of the pandemic, wich highlighted its structural limitations. However, consideration should be given to the problem of reforming these institutions bearing in mind the clinical and psychosocial dimension of users, which is constantly evolving thanks to advances in medicine. Otherwise, the changes would be technocratic and detached from the needs of users and their families.